Monopolistic Competition, Efficiency Wages and Perverse Effects of Demand Shock - Jim Malley; Hassan Molana (Center for Economic Studies and ifo Institute (CESifo), 2001)
In this paper we construct a stylised general equilibrium macromodel to show that demand led expansions may have unexpected effects when market imperfections lead to changes in labour productivity. We find some empirical support, from a number of European countries, for the main predictions of this model that unemployment and output are positively related when unemployment is low and inversely related when unemployment is high. An important policy insight that emerges from this study is that an exogenous stimulation of aggregate demand can only raise output and reduce unemployment provided the economy is operating relatively efficiently. However, when an economy is trapped in an inefficient equilibrium, positive demand shocks can lead, perversely, to an increase in unemployment.
Keywords: 330; Efficiency wages; effort supply; monopolistic competition; multiple equilibria; stability; fiscal multiplier